Hazard Analysis and Critical Control Points at Hospitals: How applied in Kendari City, Indonesia - Erwin Azizi Jayadipraja; Reslin Tobigo; Muhammad Asrullah; Anry Hariadhin Depu (Al-Sihah : The Public Health Science Journal, 2022)
Unsafe food for consumption can cause disease for humans, such as food poisoning and nosocomial infections. This study aimed to describe the implementation of Hazard Analysis and Critical Control Points (HACCP) in Hospitals in Kendari City, Indonesia. This study used analytical descriptive approach, with a survey design. It was conducted at General Hospital Bahteramas and in Kendari City General Hospital. The respondents were part of the nutrition staffs, hosts, and waiters with total of 25 people from Bahteramas General Hospital and 19 people from Kendari City General Hospital. The results revealed that the implementation of HACCP in hospitals had never been implemented effectively, at the Bahteramas General Hospital, the implementation of HACCP starting from stage 1 to stage 12 had not been entirely implemented. In addition, whilst the application of HACCP in stages 2 to 5 had been carried out at the Kendari City Hospital, the 1 and steps 6 through 12 were not applied yet. Thus, based on the concepts of food hygiene and sanitation, the hospitals must strengthen their food management efforts, in order to implement the HACCP system and for health workers, food handlers, and food servicers.